(3JfXje hGOGQI GdHfhc (B:s (3efgL hUaj JMdjdj (B/s - (3YHO GdQMje, YGWa LGHQWgs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2007)
(3jVe eaghe GdHfhc hGdfXGe GdeUQaj, GdJWhQ GdJGQjNj ddfXGe GdeUQaj GdeUQj, CfhGY hWHjYI fTGW GdHfhc, GdJfXje GdEOGQj ddHfhc GdeUQjI, EOGQI GdCUhd aj GdHfhc, GdGSJKeGQ, EOGQI GdeNGWQ aj GdHfhc, EOGQI GdQHMjI hGdSjhdI aj GdHfhc GdeUQjI, GdGFJeGfs
(3HHdjhZQGajG(B: (3U(B.323-324s
Keywords: (3GdEOGQIs; (3GdGSJKeGQs; (3GdHfhcs